CONTEMPORARY ISSUES IN TEACHING ENGLISH AS A FOREIGN LANGUAGE AT LINGUISTIC UNIVERSITIES IN UZBEKISTAN: A THEORETICAL – ANALYTICAL STUDY - Vokhidova, Tamanno (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
The teaching of English as a Foreign Language (EFL) in higher education has become a strategic priority in Uzbekistan due to globalization and educational reforms. Despite significant policy-level attention, linguistic universities and language-focused faculties continue to face systemic and pedagogical challenges. This theoretical–analytical study examines contemporary issues in EFL teaching in Uzbek linguistic higher education, including curriculum overload, theory–practice imbalance, assessment limitations, digitalization challenges, and learner motivation. Drawing on internationally recognized EFL scholarship and contextualized Uzbek academic sources, the study synthesizes existing research to identify persistent gaps between policy, theory, and classroom practice. The findings highlight the need for curriculum rebalancing, communicative-oriented pedagogy, assessment reform, and sustained teacher professional development. The study contributes to ongoing discussions on improving EFL quality in Uzbekistan and provides implications for educators, curriculum designers, and policy-makers.